TAHLIL AN-NASH FI IKHBARIYATI ASH-SHIRA' BAINA RUSIA WA UKRAINA FI SHAHIFATI BBC ARABIC NEWS BIMANDHUR TAHLIL AL-KHITHAB AN-NAQD LI TEUN A. VAN DIJK - Hasyim, Muhammad; Umam, Ahmad Zaimul; Al Anshory, Abdul Muntaqim (Annual International Conferences on Language, Literature, and Media, 2023)
This article discusses Teun A. Van Dijk's critical discourse analysis of news related to the conflict between Russia and Ukraine. The purpose of this research is to analyze and describe the structure of the text based on Teun A. Van Dijk's modern critical discourse analysis which includes macro structure, superstructure, and microstructure. This research method uses descriptive qualitative research. The research data was taken from the research object in the form of the BBC Arabic News newspaper entitled ‘Rusia wa Ukraina: Ma Alladzi yumkinu an yuhasim al-shira’ lis shalih ahad al-tharfain?. The results of this study show that the coverage in the BBC Arabic News newspaper regarding the conflict between Russia and Ukraine fulfills the three elements of Teun A. Van Dijk's model of critical discourse analysis which includes macro structure, superstructure, and microstructure. The cognition and social context of the conflict is one of the phenomena that is bad and hurts many aspects. From the data the researchers obtained, it can be concluded that the news reported regarding the development and impact of the ongoing conflict between Russia and Ukraine, aims to show that the conflict must be stopped immediately so that there are no negative things affected by the conflict.